Framing Asymmetry: Devolution and the United Kingdom’s Four Children’s Commissioners - Jane Williams (The International Journal of Children's Rights, 2016)
The United Kingdom’s four children’s commissioners, established under separate legislation for Wales, Northern Ireland, Scotland and England, are amongst the best known of the public institutions created since the beginning of devolved government in 1999. Like many such offices around the world, they are the result of domestic political and social processes as well as the influence of the requirements of international human rights treaties, specifically the United Nations Convention on the Rights of the Child. Different processes in the four countries have produced differing remits and emphases, but each commissioner is in part a response to concerns about the vulnerability of children in difficult circumstances. The commissioners’ activities include vigilance over the access of such children to support, in particular support for getting their voices heard. The commissioners have also developed prominence on the international stage as independent children’s rights institutions and all have been active in promoting children’s participation in social accountability for human rights implementation. This article explains the commissioners’ different roles and remits and examines ways in which they contribute to accountability for human rights implementation in the political, administrative, legislative, judicial and social spheres. It concludes by suggesting that their status as both ‘children’s champion’ and independent children’s rights institutions is likely to assure their long-term endurance in the still-evolving process of constitutional change in the UK.